2019
DOI: 10.1016/j.ebiom.2019.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Refining diffuse large B-cell lymphoma subgroups using integrated analysis of molecular profiles

Abstract: BackgroundGene expression profiling (GEP), next-generation sequencing (NGS) and copy number variation (CNV) analysis have led to an increasingly detailed characterization of the genomic profiles of DLBCL. The aim of this study was to perform a fully integrated analysis of mutational, genomic, and expression profiles to refine DLBCL subtypes. A comparison of our model with two recently published integrative DLBCL classifiers was carried out, in order to best reflect the current state of genomic subtypes.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 52 publications
(92 reference statements)
1
40
0
Order By: Relevance
“…Studies were included if they met the following criteria: (i) patients were newly diagnosed with primary DLBCL; (ii) gene expression profiling were conducted in pretreatment tumor tissue using the Affymetrix HU133 Plus 2.0 microarray (HG-U133 Plus_2.0); and (iii) the IPI and overall survival information were available. Five datasets were selected, GSE10846 [ 18 ], GSE31312 [ 62 ], GSE23501 [ 63 ], GSE87371 [ 64 ], and GSE98588 [ 65 ]. The selection process is illustrated in Supplementary Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Studies were included if they met the following criteria: (i) patients were newly diagnosed with primary DLBCL; (ii) gene expression profiling were conducted in pretreatment tumor tissue using the Affymetrix HU133 Plus 2.0 microarray (HG-U133 Plus_2.0); and (iii) the IPI and overall survival information were available. Five datasets were selected, GSE10846 [ 18 ], GSE31312 [ 62 ], GSE23501 [ 63 ], GSE87371 [ 64 ], and GSE98588 [ 65 ]. The selection process is illustrated in Supplementary Figure 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Gene copy number aberrations were identified by performing Comparative Genomic Hybridization (CGH) on 180 patients after whole-genome amplification, using Agilent SurePrint G3 4 × 180 K microarrays, and analysis was done with GISTIC version 2.0.22 as previously described (19). Genomic imbalance complexity was calculated as the number of all gene loci for which the GISTIC score was −2 (homozygous deletion) or +2 (copy number gain of 2+ copies).…”
Section: Analysis Of Gene Copy Number Aberrations; Bcl2 Bcl6 and Mymentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) for BCL2, BCL6, and MYC translocations was performed as previously detailed (19). Probes are listed in the Supplementary Materials and Methods.…”
Section: Analysis Of Gene Copy Number Aberrations; Bcl2 Bcl6 and Mymentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent studies that focused on the mutational landscape of DLBCLs have identified high-risk mutational profiles among DLBCLs, some of which appear COOindependent [23][24][25]. Their findings provide a rationale for targeted therapies, such as one that used clinical data in concert with DNA and gene expression analysis to identify a high-risk subgroup of patients with non-GCB DLBCLs who benefit from the addition of lenalidomide to R-CHOP [26].…”
mentioning
confidence: 99%